MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI REDOKS - Riski Resa Amanda; Bambang Suharto; Mahdian Mahdian (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. Has done research about the application of guided inquiry learning model on redox material in students of class X Social 2 SMAN 2 Banjarmasin. This research aims to determine: (1) the activities of teachers; (2) the activites of students; (3) students’ affective; (4) psychomotoric and (5) improving students learning outcomes. The research design was used classroom action research with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were 34 students of class X Social 2 SMAN 2 Banjarmasin. The results showed that an increasing teacher activity from 73,58% (good) in the first cycle to 92,96% (very good) in the second cycle, increasing students activity from 52,09% (active enough) in the first cycle to 81,21% (active) in the second cycle, increasing aspect of students' affective like character and skills from 52,82% (good enough) and 59,80% in the first cycle to 79,41% (good) and 82,35% (good) in the second cycle, increasing students psychomotoric from 67,75 (enough) in the first cycle to 80,25% (good) in the second cycle, and learning outcomes in the first cycle is 72,76 (enough) has increased in the second cycle to be 83,70 (good).Keywords: teacher activities, student activities, learning outcomes, guided inquiry learning, material of redox.